Nematocidial activity of aqueous solutions of plants of the families Cupressaceae, Rosaceae, Asteraceae, Fabaceae, Cannabaceae and Apiaceae - Boyko, Olexandra O.; Boyko, O. O.; Boyko, A. A.; Boyko, O.; Boyko, A.; Бойко, Олександра Олександрівна; Brygadyrenko, V. V.; Brygadyrenko, Victor; Brygadyrenko, Victor V.; Бригадиренко, Віктор Васильович (Oles Honchar Dnipropetrovsk National University, 2019)
In natural ecosystems of animals, introduction of larvae of parasitic nematodes into the litter layer from excrement facilitates their migration and search of new host vertebrate animals. In such conditions they are constantly affected by biologically active substances of the abundant species of plants which grow in pastures. Currently, the influence of substances present in the above-ground part of plants on the vitality of larvae of helminths in the environment remains unstudied. In this article, we present the results of our research on the nematocidial activity in vitro in the aqueous solutions of 21 species of plants distributed in the territory of Steppe Ukraine: Sanguisorba officinalis L., Rosa canina L., Crataegus sanguinea Pall., Crataegus pentagyna Waldst. & Kit. ex Willd., Armeniaca vulgaris Lam., Taraxacum officinale F. H. Wigg., Iva xanthiifolia Nutt., Artemisia campestris L., Arctium minus (Hill) Bernh., Ambrosia artemisiifolia L., Cannabis sativa L., Humulus lupulus L., Melilotus officinalis (L.) Pall., Vicia cracca L., Lotus ucrainicus Klok., Onobrychis arenaria (Kit.) DC., Foeniculum vulgare Mill., Eryngium planum L., Conium maculatum L., Juniperus communis L., Thuja occidentalis L. The level of vitality of nematode larvae of the Strongylida (Haemonchus contortus (Rudolphi, 1803)) and Rhabditida (Strongyloides papillosus (Wedl, 1856)) orders varied depending on the species of plant, and also five experimental concentrations in aqueous solutions tested in seven replications. The most notable nematocidial effect was exerted by Taraxacum officinale F. H. Wigg. – we observed death of larvae of third stage development L3H. contortus and larvae of first-third stages L1–3S. papillosus at 24 h exposure to 3% aqueous solution. Three percent aqueous solutions of S. officinalis and A. artemisiifolia displayed nematocidial properties only against S. papillosus: death of L1–3S. papillosus was observed. Aqueous solutions of R. canina, A. vulgaris, A. minus, H. lupulus, V. cracca, L. ucrainicus, O. arenaria, E. planum, C. maculatum, J. communis, Th. occidentalis had lethal effect only on non-invasive larvae (larvae of the first and second stage L1–2) of S. papillosus. They displayed no nematocidial properties towards invasive larvae of H. contortus and S. papillosus. At exposure to aqueous solutions of the rest of the studied species of plants, over 50% of L3H. contortus and L1–3S. papillosus larvae remained alive. The determined patterns allow us to state that while living in the litter and soil in the root zone of plants nematode larvae undergoa negative influence caused by some plant species. В природних екосистемах тварин введення личинок паразитичних нематод у підстилковий шар з екскрементів полегшує їх міграцію та пошук нових хребетних тварин-господарів. У таких умовах вони постійно зазнають впливу біологічно активних речовин рясних видів рослин, які ростуть на пасовищах. В даний час вплив речовин, що містяться в надземній частині рослин, на життєдіяльність личинок гельмінтів у навколишньому середовищі залишається невивченим. У цій статті ми представляємо результати наших досліджень щодо нематоцидної активності in vitro у водних розчинах 21 виду рослин, поширених на території Степової України: Sanguisorba officinalis L., Rosa canina L., Crataegus sanguinea Pall., Crataegus пентажина Вальдст. & Kit. ex Willd., Armeniaca vulgaris Lam., Taraxacum officinale FH Wigg., Iva xanthiifolia Nutt., Artemisia campestris L., Arctium minus (Hill) Bernh., Ambrosia artemisiifolia L., Cannabis sativa L., Humulus lupulus L., Melilotus officinalis (L.) Pall., Vicia cracca L., Lotus ucrainicus Klok., Onobrychis arenaria (Kit.) DC., Foeniculum vulgare Mill., Eryngium planum L., Conium maculatum L., Juniperus communis L., Thuja occidentalis L. Рівень життєздатності личинок нематод Strongylida (Haemonchus contortus (Rudolphi, 1803)) та Rhabditida (Strongyloides papillosus (Wedl, 1856)) варіювали залежно від виду рослини, а також п’ять експериментальних концентрацій у водних розчинах, випробуваних у семи повторах. Найбільш помітний нематоцидіальний ефект мав Taraxacum officinale FH Wigg. - ми спостерігали загибель личинок третього етапу розвитку L3H. контур і личинки першої-третьої стадій L1–3S. papillosus через 24 години впливу 3% водного розчину. Тривідсоткові водні розчини S. officinalis та A. artemisiifolia виявляли нематоцидні властивості лише щодо S. papillosus: загибель L1–3S. папілоз спостерігався. Водні розчини R. canina, A. vulgaris, A. minus, H. lupulus, V. cracca, L. ucrainicus, O. arenaria, E. planum, C. maculatum, J. communis, Th. occidentalis робив летальний вплив лише на неінвазивних личинок (личинки першої та другої стадії L1–2) S. papillosus. Вони не виявляли нематоцидних властивостей щодо інвазивних личинок H. contortus та S. papillosus. Під впливом водних розчинів решти досліджуваних видів рослин понад 50% L3H. contortus та L1–3S. личинки papillosus залишилися живими.
Нематоцидна активність водних розчинів рослин сімейств Cupressaceae, Rosaceae, Asteraceae, Fabaceae, Cannabaceae та Apiaceae
Бойко Олександра Олександрівна https://orcid.org/0000-0002-7299-9920
Keywords: parasitocenosis; паразитоценоз; Strongyloides papillosus; Strongyloides papillosus; Haemonchus contortus; Haemonchus contortus; aqueous solution of plants; водний розчин рослин; nematocidial properties; нематоцидні властивості